2012
DOI: 10.1117/1.jbo.17.8.085002
|View full text |Cite
|
Sign up to set email alerts
|

Effects of acetic acid on light scattering from cells

Abstract: Abstract. Acetic acid has been used for decades as an aid for the detection of precancerous cervical lesions, and the use of acetic acid is being investigated in several other tissues. Nonetheless, the mechanism of acetowhitening is unclear. This work tests some of the hypotheses in the literature and measures changes in light scattering specific to the nucleus and the cytoplasm. Wide angle side scattering from both the nucleus and the cytoplasm increases with acetic application to tumorigenic cells, with the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 30 publications
0
10
0
3
Order By: Relevance
“…The observation that light scattering can indicate metastatic efficiency suggests that the cellular organelles and processes captured by light scattering are relevant to the metastatic process (Schürmann et al, 2015). Indeed, differences in light scattering upon acetic acid treatment are often used to detect cancerous cells in patients (Marina et al, 2012). Although the mechanisms underlying light scattering of cells are unclear, intracellular organelles such as phase separated droplets (Falke et al, 2019) or lysosomes will be detected by changes to light scattering (Choi et al, 2007).…”
Section: Interpretation Of Latent Features Discriminating High and Lomentioning
confidence: 99%
“…The observation that light scattering can indicate metastatic efficiency suggests that the cellular organelles and processes captured by light scattering are relevant to the metastatic process (Schürmann et al, 2015). Indeed, differences in light scattering upon acetic acid treatment are often used to detect cancerous cells in patients (Marina et al, 2012). Although the mechanisms underlying light scattering of cells are unclear, intracellular organelles such as phase separated droplets (Falke et al, 2019) or lysosomes will be detected by changes to light scattering (Choi et al, 2007).…”
Section: Interpretation Of Latent Features Discriminating High and Lomentioning
confidence: 99%
“…The colposcope׳s magnification and fiber-optic lighting along with application of 3–5% acetic acid and/or Lugol׳s staining result in recognizable epithelial and vascular changes or characteristics associated with cervical SIL that would otherwise be invisible. The mechanism of action by which acetowhitening occurs is incompletely understood but may be caused by light scattering in dysplastic tissues, osmotic shifts, and/or changes in cytokeratin expression causing lesions to turn white when acetic acid applied and can thus be recognized as potentially abnormal and targeted for biopsy [14] , [15] . Like acetic acid, Lugol׳s staining is used in cervical colposcopy to help differentiate cHSIL from cLSIL and to determine the lesion margins for treatment.…”
Section: Introductionmentioning
confidence: 99%
“…More advanced fibre optic probes for PLSS made use of gradient-index (GRIN) lens to implement depth selective measurement from a range of near surface depths (100-200 mm) to interrogate blood supply [66,67]. A great number of translational studies for diagnosis of breast cancer [68], prostate cancer [69], intraoperative determination of sentinel lymph node status in the breast [70], colonic lesions [71], oral premalignancy [72], high grade dysplasia and cancer in Barrett's oesophagus [73,74], cervix neoplasia [75,76], investigation of the nature of aceto-whitening in cervix cancer inspection [77][78][79][80][81][82], gold nanoparticle sizing [83], and monitoring apoptosis in cell cultures [84][85][86] have demonstrated that LSS provides a promising solution for cell culture monitoring, tissue surveillance and biopsy guidance in a relatively simple and cost effective configuration.…”
Section: Polarized Light and Biological Tissuementioning
confidence: 99%